Knowledge, Attitude and Practice of Pharmacovigilance Among Libyan Pharmacists in Benghazi - Senussi, Abdelhamid; Azza Grew (AlQalam Journal of Medical and Applied Sciences, 2024)
Pharmacovigilance is meant to ensure patients’ safety from adverse drug reaction (ADR). This study aims to assess knowledge, attitude and practice of pharmacovigilance and ADR reporting among pharmacists in Benghazi- Libya. A cross-sectional questionnaire-based study involving knowledge, attitude and practice of pharmacovigilance and it targeted 93 pharmacists at Benghazi medical center. The study showed that pharmacists’ knowledge was 63%, and their attitude was positive. However, their practice was clearly poor. The present study illustrated that there is a need for immediate improvement of ADR monitoring and the importance of CME on pharmacovigilance programs. اليقظة الدوائية تعنى بتأكيد سلامة المرضى من الأعراض الجانبية للأدوية وهذه الدراسة جاءت لقياس مدى معرفة وتوجهات وممارسات الصيادلة في بنغازي بمفهوم اليقظة الدوائية. استخدمت دراسة مقطعية باستبيان وشملت 93 صيدلي في مركز بنغازي الطبي. أوضحت الدراسة ان معرفة الصيادلة باليقظة الدوائية 63% وتوجهاتهم إيجابية ولكن هناك قصور واضح بما يخص ممارستهم. أوضحت هذه الدراسة الحاجة العاجلة لتحسين مراقبة الأعراض الجانبية للأدوية والحاجة الى التعليم الطبي المستمر بما يخص برنامج اليقظة الدوائية